Answer:
There is no horizontal asymptote for the function f(x).
Step-by-step explanation:
We have the function
. Notice that if
the function is not defined, because the denominator of the fractions equals zero, and the numerator don't. This fact is equivalent to the existence of a vertical asymptote at
. In mathematical language:
![\lim_{x\rightarrow 8^+} \frac{x^2+6x-8}{x-8} = +\infty](https://tex.z-dn.net/?f=%5Clim_%7Bx%5Crightarrow%208%5E%2B%7D%20%5Cfrac%7Bx%5E2%2B6x-8%7D%7Bx-8%7D%20%3D%20%2B%5Cinfty)
and
![\lim_{x\rightarrow 8^-} \frac{x^2+6x-8}{x-8} = -\infty.](https://tex.z-dn.net/?f=%5Clim_%7Bx%5Crightarrow%208%5E-%7D%20%5Cfrac%7Bx%5E2%2B6x-8%7D%7Bx-8%7D%20%3D%20-%5Cinfty.)
Now, in case that f(x) has an horizontal asymptote the following must hold:
![\lim_{x\rightarrow +\infty} \frac{x^2+6x-8}{x-8} = L\in\mathbb{R}](https://tex.z-dn.net/?f=%5Clim_%7Bx%5Crightarrow%20%2B%5Cinfty%7D%20%5Cfrac%7Bx%5E2%2B6x-8%7D%7Bx-8%7D%20%3D%20L%5Cin%5Cmathbb%7BR%7D)
But, actually
![\lim_{x\rightarrow \infty} \frac{x^2+6x-8}{x-8} = \infty.](https://tex.z-dn.net/?f=%5Clim_%7Bx%5Crightarrow%20%5Cinfty%7D%20%5Cfrac%7Bx%5E2%2B6x-8%7D%7Bx-8%7D%20%3D%20%5Cinfty.)
Hence, there is no horizontal asymptote.
Anyway, f(x) has an asymptote, but no horizontal. In order to obtain the slope of the asymptote, we need to find the following limit:
![\lim_{x\rightarrow +\infty} = \frac{f(x)}{x} = \lim_{x\rightarrow +\infty} \frac{x^2+6x-8}{x(x-8)} = \frac{x^2+6x-8}{x^2-8x} = 1.](https://tex.z-dn.net/?f=%5Clim_%7Bx%5Crightarrow%20%2B%5Cinfty%7D%20%3D%20%5Cfrac%7Bf%28x%29%7D%7Bx%7D%20%3D%20%5Clim_%7Bx%5Crightarrow%20%2B%5Cinfty%7D%20%5Cfrac%7Bx%5E2%2B6x-8%7D%7Bx%28x-8%29%7D%20%3D%20%5Cfrac%7Bx%5E2%2B6x-8%7D%7Bx%5E2-8x%7D%20%3D%201.)
Then asymptote has equation
. To find
we calculate the limit
![\lim_{x\rightarrow +\infty} (f(x)-mx) = \lim_{x\rightarrow +\infty} \frac{x^2+6x-8}{x-8} -x = \lim_{x\rightarrow +\infty} \frac{14x-8}{x-8} = 14](https://tex.z-dn.net/?f=%5Clim_%7Bx%5Crightarrow%20%2B%5Cinfty%7D%20%28f%28x%29-mx%29%20%3D%20%5Clim_%7Bx%5Crightarrow%20%2B%5Cinfty%7D%20%5Cfrac%7Bx%5E2%2B6x-8%7D%7Bx-8%7D%20-x%20%3D%20%5Clim_%7Bx%5Crightarrow%20%2B%5Cinfty%7D%20%5Cfrac%7B14x-8%7D%7Bx-8%7D%20%3D%2014)
Hence, the asymptote at
is
.